Answer:
r = 2, s = - 1
Explanation:
Given the 2 equations
2r + 8s = - 4 → (1)
7r = - 6s + 8 ( add 6s to both sides )
7r + 6s = 8 → (2)
Multiplying (1) by 7 and (2) by - 2, then adding will eliminate the r- term
14r + 56s = - 28 → (3)
- 14r - 12s = - 16 → (4)
Add (3) and (4) term by term to eliminate r , that is
44s = - 44 ( divide both sides by 44 )
s = - 1
Substitute s = - 1 into either of the 2 equations and solve for r
Substituting into (1)
2r + 8(- 1) = - 4
2r - 8 = - 4 ( add 8 to both sides )
2r = 4 ( divide both sides by 2 )
r = 2
solution is r = 2 , s = - 1